Novel nelfinavir mesylate loaded d-α-tocopheryl polyethylene glycol 1000 succinate micelles for enhanced pediatric anti HIV therapy: In vitro characterization and in vivo evaluation - Moretton, Marcela Analía (2014)
Worldwide more than 35 million people are living with Human Immunodeficiency Virus (HIV) where 3.3 million are children. This translates in approximately 700 new daily infections in children only in 2012. Prolonged High Activity Antiretroviral Therapy (HAART) regimes could present low-patient compliance, especially in children, affecting therapeutic success. Nelfinavir mesylate (NFV) is a non-peptidic HIV-1 protease inhibitor (IP) which was the first IP recommended for pediatric use (>2 years-old). It exhibits pH-dependant aqueous solubility which results highly restricted at physiological pH values. The former represents a main clinical limitation due to the reduction on drug absorption along the small intestine after an oral administration, leading to unpredictable drug bioavailability. Moreover a liquid formulation of NFV is not available worldwide, preventing appropriate dose adjustment and more convenient administration. In this framework, the present investigation reports the development of a NFV highly concentrated aqueous formulation for a more appropriate management of pediatric anti-HIV therapy. The aim was to encapsulate NFV within d-α-tocopheryl polyethylene glycol 1000 succinate micelles to improve its aqueous solubility and its oral pharmacokinetic parameters. Results show that NFV aqueous solubility was increased up to 80.3. mg/mL. NFV-loaded micelles exhibited a hydrodynamic diameter of 5.6. nm and a spherical morphology as determined by dynamic light scattering and transmission electronic microscopy, respectively. In vitro NFV release profile demonstrated a cumulative drug release of 56% at 6. h. Finally, in vivo data showed a significant (. p<. 0.01) increase of Area-Under-the-Curve between 0 and 24. h for NFV encapsulated in micelles in comparison with a NFV suspension prepared with glycerin 20% v/v and carboxymethylcellulose sodium 0.5% w/v, representing an increment on drug oral relative bioavailability of 1.71-fold. Thereby, this formulation represents an innovative nanotechnological platform to improve pediatric HIV pharmacotherapy.